CANVA APPLICATION INTEGRATION AS A DIGITAL INNOVATION TO IMPROVE TEACHER CREATIVITY IN KKG KENANGA - Desnora Sahriaty Siregar; Nur Asiah Jamil Nasution; Cindy Ayu Lestari; Hamka (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to describe the integration of the Canva application as a digital innovation to enhance teacher creativity in the Kenanga Teacher Working Group (KKG). The background of this research stems from the need for teachers to adapt to developments in educational technology and create learning media that are engaging, interactive, and relevant to the characteristics of 21st-century learners. The research method used was descriptive qualitative, with teachers who were members of the Kenanga KKG. Data were collected through observation, interviews, and documentation of training activities and the implementation of Canva in the learning process. The results indicate that the use of Canva can improve teachers' abilities in designing creative and communicative digital learning media. Furthermore, the collaborative training and mentoring activities within the KKG also fostered increased digital competence and teachers' confidence in innovation. Thus, the integration of Canva within the Kenanga KKG environment has proven effective as an effort to strengthen teacher professionalism in the digital era.